2020
DOI: 10.1002/ctm2.14
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab plus ipilimumab versus pembrolizumab as chemotherapy‐free, first‐line treatment for PD‐L1‐positive non‐small cell lung cancer

Abstract: Background Nivolumab plus ipilimumab (N‐I) or pembrolizumab (PEM) is associated with survival improvement as chemotherapy‐free, first‐line treatment for patients with advanced non‐small cell lung carcinoma (NSCLC) and positive programmed cell death ligand 1 (PD‐L1). However, no direct comparison data exist between these two regimens to inform clinical decisions. Therefore, we performed indirect comparison for N‐I versus PEM using frequentist methods. Results Three randomized trials (KEYNOTE‐024, KEYNOTE‐042, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 11 publications
2
26
1
Order By: Relevance
“…PFS and OS HRs were estimated using inversevariance weighting, and treatment-related AEs (TRAEs) were compared using the Mantel-Haenszel method. The study found no significant differences in OS, with an HR of 0.98 (95% CI 0.77-1.24) for nivolumab plus ipilimumab versus pembrolizumab, consistent with the findings by Halmos et al [10,11]. The PFS HR of nivolumab plus ipilimumab versus pembrolizumab was estimated to be 0.77 (95% CI 0.62-0.95) by Zhou et al indicating a larger and statistically significant difference in treatment effects on PFS between the two regimens compared with what was detected by Halmos et al [10,11].…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…PFS and OS HRs were estimated using inversevariance weighting, and treatment-related AEs (TRAEs) were compared using the Mantel-Haenszel method. The study found no significant differences in OS, with an HR of 0.98 (95% CI 0.77-1.24) for nivolumab plus ipilimumab versus pembrolizumab, consistent with the findings by Halmos et al [10,11]. The PFS HR of nivolumab plus ipilimumab versus pembrolizumab was estimated to be 0.77 (95% CI 0.62-0.95) by Zhou et al indicating a larger and statistically significant difference in treatment effects on PFS between the two regimens compared with what was detected by Halmos et al [10,11].…”
Section: Introductionsupporting
confidence: 88%
“…The study found no significant differences in OS, with an HR of 0.98 (95% CI 0.77-1.24) for nivolumab plus ipilimumab versus pembrolizumab, consistent with the findings by Halmos et al [10,11]. The PFS HR of nivolumab plus ipilimumab versus pembrolizumab was estimated to be 0.77 (95% CI 0.62-0.95) by Zhou et al indicating a larger and statistically significant difference in treatment effects on PFS between the two regimens compared with what was detected by Halmos et al [10,11]. We speculate the different finding in PFS might be due to the following reasons: the MAIC conducted by Halmos et al reduced cross-trial differences by adjusting the IPD of KEYNOTE-024 and -042 to match the baseline characteristics of patients in CheckMate 227 Part 1a, making its HR estimates more robust than the HRs estimated by Zhou et al [10,11].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the last decade, better biochemical insights into KRAS structural biology finally allowed researchers to develop direct KRAS(G12C) inhibitors like the preclinical compounds SML-8-73-1, compound 12 ("Shokat compound"), ARS-853 and ARS-1620, as well as the clinical compounds AMG-510 (Amgen), MRTX-849 (Mirati Immune checkpoint inhibitors (ICIs) block the PDL1-PD1 receptor interaction and thus can reinvigorate antitumor immune responses in some patients with so-called "hot" tumors. ICIs alone or in combination with chemotherapy have become standard-of-care treatment for NSCLC patients whose tumors express PDL1 and lack EGFR mutations or EML4/ALK rearrangements [94][95][96][97][98][99]. These immunologically "hot" tumors are characterized by the accumulation of proinflammatory cytokines, high PD-L1 expression and intratumoral accumulation of CD8+ tumor-infiltrating lymphocytes (TILs), which are required for ICIs to be effective [100].…”
Section: Efficacy Of Direct Kras(g12c) Inhibitors and Mechanisms Of Rmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) block the PDL1–PD1 receptor interaction and thus can reinvigorate antitumor immune responses in some patients with so-called “hot” tumors. ICIs alone or in combination with chemotherapy have become standard-of-care treatment for NSCLC patients whose tumors express PDL1 and lack EGFR mutations or EML4/ALK rearrangements [ 94 , 95 , 96 , 97 , 98 , 99 ]. These immunologically “hot” tumors are characterized by the accumulation of proinflammatory cytokines, high PD-L1 expression and intratumoral accumulation of CD8+ tumor-infiltrating lymphocytes (TILs), which are required for ICIs to be effective [ 100 ].…”
Section: Mutant Kras Proteins Orchestrate the Tmentioning
confidence: 99%